Análise das competências organizacionais para a internacionalização: o caso Vulcabras/Azaleia - Suzin, Juliana Ballin (Universidade do Vale do Rio do Sinos, 2010)
The aim of this research was to analyze organizational capabilities on the internationalization process of a shoe company. Such objective is sustained by contemporary theories which lead to the development of organizational capabilities can become into a more efficient and efficacious internationalization strategy. Based on these theories, it´s assumed there´s an articulation of resources through the organizational structure which can promote the development of capabilities in internationalized organizations with a bigger efficiency and efficaciously. In order to reach the proposed goals, the search was made through a single study-case in the biggest shoe company of Latin America, Vulcabras/Azaleia. The choice of the search field relied on the company´s features and on its international performance with pertinent data to answer the problems proposed for this study. The search intends to contribute to deeper studies of theories about the analysis of companies´ internal environment through the identification of
Keywords: aprendizagem; competências organizacionais; estratégia; indústria calçadista; internacionalização; learning; organizational capabilities; shoe industry; strategy; internationalization; Ciências Sociais Aplicadas